2010
DOI: 10.1007/s00404-010-1403-7
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual phase-related differences in the pulsatility index on the central retinal artery suggest an oestrogen vasodilatation effect that antagonizes with progesterone

Abstract: Our results suggest the existence of an oestrogen vasodilatation effect on the central retinal artery that is menstrual phase-related and antagonized by progesterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Another study that evaluated the effect of ovarian steroids on the vascular resistance of the CRA also suggested the existence of an estrogen vasodilatation effect because a reduction in PI during the follicular phase of ovulatory women was observed. 16 Therefore, we performed this study to evaluate the effect of estrogen on the vascular resistance of the CRA in postmenopausal women, compared with placebo, using transorbital ultrasound with Doppler fluxometry. The results not only may increase our understanding of the effects of reproductive hormones on the central nervous system but can also help elucidate the pathogenesis of migraine, premenstrual syndrome, and loss of cognitive function and diseases, such as stroke and Alzheimer disease.…”
mentioning
confidence: 99%
“…Another study that evaluated the effect of ovarian steroids on the vascular resistance of the CRA also suggested the existence of an estrogen vasodilatation effect because a reduction in PI during the follicular phase of ovulatory women was observed. 16 Therefore, we performed this study to evaluate the effect of estrogen on the vascular resistance of the CRA in postmenopausal women, compared with placebo, using transorbital ultrasound with Doppler fluxometry. The results not only may increase our understanding of the effects of reproductive hormones on the central nervous system but can also help elucidate the pathogenesis of migraine, premenstrual syndrome, and loss of cognitive function and diseases, such as stroke and Alzheimer disease.…”
mentioning
confidence: 99%
“…It has already been demonstrated that estradiol decreases the vascular resistance of cerebral vessels in premenopausal women 20 and thus increases resistance during menopause. 23,24 Therefore, only postmenopausal and nonobese women who were not using hormones were evaluated to avoid having the possible effects of endogenous estrogen cause any bias to the study.…”
Section: Discussionmentioning
confidence: 99%
“…25 We decided to study central retinal and ophthalmic arteries because they are functionally and anatomically identical to other cerebral arteries of a similar size. 26,27 In addition, the easy access allows the evaluation to be performed directly on the arterial vascular bed 19,20,28 and to be repeated by others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations